The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsinfecdis.0c00526
|View full text |Cite
|
Sign up to set email alerts
|

A Glance at Antimicrobial Strategies to Prevent Catheter-Associated Medical Infections

Abstract: Urinary and intravascular catheters are two of the most used invasive medical devices; however, microbial colonization of catheter surfaces is responsible for most healthcare-associated infections (HAIs). Several antimicrobial-coated catheters are available, but recurrent antibiotic therapy can decrease their potential activity against resistant bacterial strains. The aim of this Review is to question the actual effectiveness of currently used (coated) catheters and describe the progress and promise of alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 193 publications
0
32
0
Order By: Relevance
“…Moreover, for the interaction between BAC molecules and bacteria to occur, the particles need to be in close contact with bacteria. Of course, the BAC molecules inside the pores will not be readily available for bacteria [ 62 ], since the particles are mesoporous (pore diameters between 2 and 50 nm [ 63 ]) and bacteria (due to their bigger size) cannot enter the pores. In the work of He et al [ 56 ], they found that bacteria are dead upon contact with the immobilized QACs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for the interaction between BAC molecules and bacteria to occur, the particles need to be in close contact with bacteria. Of course, the BAC molecules inside the pores will not be readily available for bacteria [ 62 ], since the particles are mesoporous (pore diameters between 2 and 50 nm [ 63 ]) and bacteria (due to their bigger size) cannot enter the pores. In the work of He et al [ 56 ], they found that bacteria are dead upon contact with the immobilized QACs.…”
Section: Resultsmentioning
confidence: 99%
“…Extended spectrum β-lactamase (ESBL) and carbapenemase producing Gram negative bacteria have emerged as a recalcitrant therapeutic challenge. These MDR microbes are the most notorious group of bacteria that pose a serious global health threat [ 32 , 33 ]. We found that our antimicrobial biomaterials ( PDMS-PIM1 ) inhibited the growth of all the ESKAPE group of clinical isolates as well as MRSA and Vancomycin-resistant Enterococcus ( VRE ) pathogens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most clinically relevant aspects of biomaterial-related infection control is that of catheter-associated infections. As reviewed by Ricado et al , despite several decades of intensive research and development involving those strategies discussed in the previous sections, and others, efficacy data obtained from in vitro studies is not properly reflected in the clinical setting [ 133 ].…”
Section: Categories Of Bioactive Materialsmentioning
confidence: 99%